STRATEGI GURU FIKIH DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIKIH DI MADRASAH ALIYAH PESANTREN MIZANUL ‘ULUM SANROBONE KABUPATEN TAKALAR - Asmi; Hasibuddin; Ratika Nengsi; Rosmiati; Subaedah; M Akil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims : (1) to analyze the strategies of Fiqh teachers in improving student learning outcomes at the Mizanul Ulum Sanrobone Islamic Boarding School, Takalar Regency. (2) to identify the supporting and inhibiting factors of Fiqh teachers' strategies in improving student learning outcomes at the Mizanul Ulum Sanrobone Islamic Boarding School, Takalar Regency.The research method used was descriptive qualitative with a phenomenological approach. Data were collected through observation, interviews, and documentation. Data analysis techniques included data collection, data presentation, data reduction, and conclusion drawing.The results of the study indicate that: (1) fiqh teachers use varied learning strategies, which include demonstration methods, group discussions, questions and answers, assignments, use of learning media, and evaluation. This strategy has been proven to improve cognitive understanding, practical skills, as well as student motivation and activeness. Supporting factors found include teacher competence, student motivation and active participation, and the Islamic boarding school environment. (2) Inhibiting factors include limited facilities and infrastructure, differences in student ability levels, and limited learning time. This study recommends that teachers continue to develop varied learning methods, schools improve technology facilities and training, and future researchers can develop digital technology-based learning strategies to enrich the effectiveness of fiqh learning.